A tubular graphyne-coated bismuth particle nanomaterial and its preparation method and application
By using tubular graphiteyne to coat bismuth particle nanomaterials in sodium ion batteries, the performance attenuation problem caused by volume changes during charging and discharging of bismuth materials is solved, and the high specific capacity and power density are improved, which significantly improves the battery's Cyclic stability.
Patent Information
- Application Number
- CN202210784986.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-05
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-07-05
AI Technical Summary
The volume of the negative electrode material of sodium ion battery changes dramatically during charging and discharging, resulting in rapid attenuation of battery performance, limiting its application.
The nanomaterial of graphite-coated bismuth particles is prepared by using tubular graphite-coated copper nanowires catalyzed by a copper catalyst to prepare graphite-coated copper nanowires, and the copper is replaced with bismuth through an electrochemical replacement reaction to form graphite-coated bismuth particles. Ensure that the material does not deviate from the conductive network during charging and discharging.
It improves the specific capacity and power density of sodium ion/lithium ion batteries, realizes high capacity output at ultra-fast discharge rates, and improves rate performance and cycle stability.
Smart Images

Figure HDA0003731576550000011 
Figure HDA0003731576550000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a tubular graphyne-coated bismuth particle nanomaterial, a preparation method and an application thereof. Background Art
[0002] Sodium-ion batteries are expected to play an important role in large-scale energy storage due to their abundant natural sodium resources, low cost, long cycle life, high rate capability and high safety. Therefore, the development of high-performance sodium-ion batteries has become the focus of the energy storage field. Considerable progress has been made in the positive electrode materials of sodium-ion batteries, but the research on negative electrode materials is very limited, which seriously hinders the development of high-power sodium-ion batteries.
[0003] Bismuth metal is a promising negative electrode material for sodium-ion batteries due to its unique layered crystal structure and large interlayer spacing. Bismuth changes dramatically in volume during the charge and discharge process, which causes rapid degradation of battery performance and limits the application of this type of material in sodium-ion batteries. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides a tubular graphyne-coated bismuth particle nanomaterial and its preparation method and application, which can effectively solve the problem that the existing bismuth material has a large volume change during charging and discharging, resulting in rapid performance degradation.
[0005] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0006] A method for preparing a tubular Graphene-coated Bismuth particle nanomaterial comprises the following steps:
[0007] (1) using a copper catalyst to catalyze the precursor to perform an alkyne-alkyne coupling reaction to prepare a graphene-coated copper nanomaterial;
[0008] (2) The metal copper in the graphyne-coated copper nanowires is replaced with metal bismuth by an electrochemical replacement reaction.
[0009] Furthermore, the copper catalyst in step (1) comprises copper nanowires and copper nanoblocks, and the diameter of the copper nanowires is 10-200 nm and the length is 0.1-100 μm.
[0010] Furthermore, the alkyne-alkyne coupling reaction process in step (1) is as follows: adding the copper catalyst and the precursor to an acetone / pyridine reaction solvent, stirring the reaction for 24-72 hours, and obtaining the graphyne-coated copper nanomaterial.
[0011] Furthermore, the molar ratio of copper to the precursor in the copper catalyst is 1:10-100, and the concentration of the precursor in the solution is 0.01-500 mg / mL.
[0012] Furthermore, the precursor is ethynylbenzene, and the volume ratio of acetone to pyridine in the reaction solvent is 1:0.1-1.
[0013] Further, ethynylbenzene is prepared by deprotecting hexa((trimethylsilyl)ethynyl)benzene, 1,3,5-(trimethylsilyl)ethynyl-2,4,6-triazine, 1,3,5-(trimethylsilyl)ethynyl-2,4,6-trifluorobenzene, 1,3,5-(trimethylsilyl)ethynyl-2,4,6-trichlorobenzene or 1,3,5-((trimethylsilyl)ethynyl)benzene, and the precursor is specifically hexaethynylbenzene, 1,3,5-ethynyl-2,4,6-triazine, 1,3,5-ethynyl-2,4,6-trifluorobenzene, 1,3,5-ethynyl-2,4,6-trichlorobenzene or 1,3,5-ethynylbenzene.
[0014] Furthermore, the specific operation in step (2) is as follows: BiI3 is added to 1,3-dimethylpropylene urea to dissolve, and then tetrabutylammonium tetrafluoroborate is added thereto to obtain a BiI3 mixed solution, and the BiI3 solution is mixed with the graphyne-coated copper nanomaterial in step (1), and the reaction is stirred to obtain.
[0015] Furthermore, the concentration of BiI3 in the BiI3 mixed solution is 0.01-10 mol / L, and the concentration of tetrabutylammonium tetrafluoroborate is 0.01-1 mol / L.
[0016] Furthermore, in the reaction of step (2), the molar ratio of copper to bismuth is 1:1-10.
[0017] A tubular graphyne-coated bismuth particle nanomaterial is prepared by adopting the above method.
[0018] Application of the above tubular Graphene coated Bismuth particle nanomaterial in the preparation of sodium ion battery negative electrode material or lithium ion battery negative electrode material
[0019] The beneficial effects of this application are:
[0020] In this application, bismuth is prepared into Graphene coated bismuth nanomaterials. The confinement effect of the Graphene shell can continue to coat the pulverized material in the conductive network, so that the pulverized material does not separate from the conductive network, and can still be charged and discharged normally, which can effectively prevent the material from being separated from the conductive network due to volume changes; the traditional carbon shell itself has a low storage capacity and lacks ion diffusion channels. The composite of the traditional carbon shell and bismuth-based materials will greatly reduce the total specific capacity of the material and limit the rapid transmission of ions. However, in the materials of this application, Graphene not only has a higher theoretical specific capacity, but also has a wider ion diffusion channel, which can break through the bottleneck of low capacity and low ion diffusion coefficient of the traditional carbon shell, thereby improving the power density of sodium ion / lithium ion batteries. The materials in this application not only improve the specific capacity, but also accelerate ion diffusion, which can achieve high capacity output at ultrafast discharge rate and improve power density. When the materials in this application are used as the negative electrode materials of sodium ion batteries or lithium ion batteries, the sodium ion batteries or lithium ion batteries have good rate performance, ultra-long cycle stability and high specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The X-ray diffraction spectrum (XRD) of the tubular graphyne-coated bismuth particle nanomaterial in Example 1;
[0022] Figure 2 This is a transmission electron microscope image of the tubular graphyne-coated bismuth particle nanomaterial in Example 1. DETAILED DESCRIPTION
[0023] The specific implementation modes of the present invention are described in detail below with reference to the accompanying drawings.
[0024] Example 1
[0025] A tubular Graphene coated Bismuth particle nanomaterial, the preparation method of which comprises the following steps:
[0026] (1) adding copper nanowires with a diameter of 50 nm and deprotected hexa((trimethylsilyl)ethynyl)benzene (the molar ratio of copper nanowires to hexa((trimethylsilyl)ethynyl)benzene is 1:30) to a mixed solution prepared by acetone and pyridine in a volume ratio of 10:1, wherein the concentration of the precursor in the acetone / pyridine mixed solution is 0.01 mg / mL, and then stirring on a magnetic stirrer at a stirring speed of 100 rpm for 36 hours, washing the reaction product with ethanol, centrifuging, and vacuum drying to obtain a graphyne-coated copper nanowire material (product A);
[0027] (2) BiI3 is added to 1,3-dimethylpropyleneurea to dissolve, and then tetrabutylammonium tetrafluoroborate is added thereto to prepare a BiI3 mixed solution (solution B), wherein the concentration of tetrabutylammonium tetrafluoroborate (TBABF4) in the mixed solution is 0.1 mol / L, and the concentration of BiI3 is 1 mol / L. The BiI3 mixed solution (solution B) and the graphyne-coated copper nanomaterial (product A) in step (1) are mixed on a magnetic stirrer and stirred, wherein the molar ratio of copper to bismuth in the mixed solution is 1:2, the stirring speed is 100 rpm, the reaction is carried out for 72 hours, the product is washed with ethanol, centrifuged, and a tubular graphyne-coated bismuth particle nanomaterial is obtained by vacuum drying.
[0028] (3) Tubular graphyne-coated bismuth particle nanomaterials, carbon black and sodium carboxymethyl cellulose (CMC) were prepared into a slurry in a mass ratio of 7:2:1 and coated on copper foil. The slurry was assembled with sodium metal foil into a half-cell. The separator was glass fiber and the electrolyte was 1M NaPF6 in ethylene glycol dimethyl ether solution. The electrochemical performance of the battery was investigated. -1 At the current density, the capacity is 347mA hg -1 , at 150A g -1 At ultra-high current density, the capacity is 291mA hg -1 , at 10A g -1 After 10,000 cycles at high current density, the capacity retention rate is as high as 98%.
[0029] Example 2
[0030] A tubular Graphene coated Bismuth particle nanomaterial, the preparation method of which comprises the following steps:
[0031] (1) adding copper nanowires with a diameter of 10 nm and deprotected hexa((trimethylsilyl)ethynyl)benzene (the molar ratio of copper nanowires to hexa((trimethylsilyl)ethynyl)benzene is 1:100) to a mixed solution prepared by acetone and pyridine in a volume ratio of 5:1, wherein the concentration of the precursor in the acetone / pyridine mixed solution is 500 mg / mL, and then stirring on a magnetic stirrer at a stirring speed of 200 rpm for 72 hours, washing the reaction product with ethanol, centrifuging, and vacuum drying to obtain a graphyne-coated copper nanowire material (product A);
[0032] (2) BiI3 is added to 1,3-dimethylpropyleneurea to dissolve, and then tetrabutylammonium tetrafluoroborate is added thereto to prepare a BiI3 mixed solution (solution B), wherein the concentration of tetrabutylammonium tetrafluoroborate (TBABF4) in the mixed solution is 0.01 mol / L, and the concentration of BiI3 is 0.1 mol / L. The BiI3 mixed solution (solution B) and the graphyne-coated copper nanomaterial (product A) in step (1) are mixed on a magnetic stirrer and stirred, wherein the molar ratio of copper to bismuth in the mixed solution is 1:1.5, the stirring speed is 100 rpm, the reaction is carried out for 54 hours, the product is washed with ethanol, centrifuged, and a tubular graphyne-coated bismuth particle nanomaterial is obtained by vacuum drying.
[0033] (3) Tubular graphyne-coated bismuth particle nanomaterials, carbon black and sodium carboxymethyl cellulose (CMC) were prepared into a slurry in a mass ratio of 7:2:1 and coated on copper foil. The slurry was assembled with sodium metal foil into a half-cell. The separator was glass fiber and the electrolyte was 1M NaPF6 in diethylene glycol dimethyl ether solution. The electrochemical performance of the battery was investigated. -1 At the current density, the capacity is 337mA hg -1 , at 150A g -1 At ultra-high current density, the capacity is 274mA hg -1 , at 10A g -1 After 15,000 cycles at high current density, the capacity retention rate is as high as 96%.
[0034] Example 3
[0035] A tubular Graphene coated Bismuth particle nanomaterial, the preparation method of which comprises the following steps:
[0036] (1) adding copper nanowires with a diameter of 100 nm and deprotected 1,3,5-(trimethylsilyl)ethynyl-2,4,6-trifluorobenzene (the molar ratio of copper nanowires to 1,3,5-(trimethylsilyl)ethynyl-2,4,6-trifluorobenzene is 1:50) to a mixed solution prepared by acetone and pyridine in a volume ratio of 2:1, wherein the concentration of the precursor in the acetone / pyridine mixed solution is 4 mg / mL, and then stirring on a magnetic stirrer at a stirring speed of 100 rpm for 72 hours, washing the reaction product with ethanol, centrifuging, and vacuum drying to obtain a graphyne-coated copper nanowire material (product A);
[0037] (2) adding BiI3 to 1,3-dimethylpropyleneurea to dissolve, and then adding tetrabutylammonium tetrafluoroborate thereto to obtain a BiI3 mixed solution (solution B), wherein the concentration of tetrabutylammonium tetrafluoroborate (TBABF4) in the mixed solution is 1 mol / L, and the concentration of BiI3 is 0.01 mol / L, and the BiI3 mixed solution (solution B) and the graphyne-coated copper nanomaterial (product A) in step (1) are mixed on a magnetic stirrer and stirred, wherein the molar ratio of copper to bismuth in the mixed solution is 1:1, and the stirring speed is 100 rpm. The reaction is carried out for 54 hours, and the product is washed with ethanol, centrifuged, and vacuum dried to obtain a tubular graphyne-coated bismuth particle nanomaterial;
[0038] (3) Tubular graphyne-coated bismuth particle nanomaterials, carbon black and sodium carboxymethyl cellulose (CMC) were prepared into a slurry in a mass ratio of 9:0.5:0.5 and coated on copper foil. The slurry was assembled with sodium metal foil into a half-cell. The separator was glass fiber and the electrolyte was 1M NaPF6 in ethylene glycol dimethyl ether solution. The electrochemical performance of the battery was investigated. -1 At the current density, the capacity is 332mA hg -1 , at 150A g -1 At ultra-high current density, the capacity is 265mA hg -1 , at 10A g -1 After 20,000 cycles at high current density, the capacity retention rate is as high as 94%.
[0039] Example 4
[0040] A tubular Graphene coated Bismuth particle nanomaterial, the preparation method of which comprises the following steps:
[0041] (1) adding copper nanowires with a diameter of 200 nm and deprotected 1,3,5-(trimethylsilyl)ethynyl-2,4,6-trichlorobenzene (the molar ratio of copper nanowires to 1,3,5-(trimethylsilyl)ethynyl-2,4,6-trichlorobenzene is 1:10) to a mixed solution prepared by acetone and pyridine in a volume ratio of 1:1, wherein the concentration of the precursor in the acetone / pyridine mixed solution is 4 mg / mL, and then stirring on a magnetic stirrer at a stirring speed of 100 rpm for 72 hours, washing the reaction product with ethanol, centrifuging, and vacuum drying to obtain a graphyne-coated copper nanowire material (product A);
[0042] (2) BiI3 is added to 1,3-dimethylpropyleneurea to dissolve, and then tetrabutylammonium tetrafluoroborate is added thereto to prepare a BiI3 mixed solution (solution B), wherein the concentration of tetrabutylammonium tetrafluoroborate (TBABF4) in the mixed solution is 0.1 mol / L, and the concentration of BiI3 is 10 mol / L. The BiI3 mixed solution (solution B) and the graphyne-coated copper nanomaterial (product A) in step (1) are mixed on a magnetic stirrer and stirred, wherein the molar ratio of copper to bismuth in the mixed solution is 1:10, the stirring speed is 100 rpm, the reaction is carried out for 72 hours, the product is washed with ethanol, centrifuged, and a tubular graphyne-coated bismuth particle nanomaterial is obtained by vacuum drying.
[0043] (3) Tubular graphyne-coated bismuth particle nanomaterials, carbon black and sodium carboxymethyl cellulose (CMC) were prepared into a slurry in a mass ratio of 9:0.5:0.5 and coated on copper foil. The slurry was assembled with lithium metal foil into a half-cell. The separator was glass fiber and the electrolyte was 2M LiPF6 in ethylene glycol dimethyl ether solution. The electrochemical performance of the battery was investigated. -1 At the current density, the capacity is 351mA hg -1 , at 150A g -1 At ultra-high current density, the capacity is 294mA hg -1 , at 10A g -1 After 25,000 cycles at high current density, the capacity retention rate is as high as 94%.
[0044] Example 5
[0045] A tubular Graphene coated Bismuth particle nanomaterial, the preparation method of which comprises the following steps:
[0046] (1) adding copper nanowires with a diameter of 150 nm and deprotected 1,3,5-((trimethylsilyl)ethynyl)benzene (the molar ratio of copper nanowires to 1,3,5-((trimethylsilyl)ethynyl)benzene is 1:60) to a mixed solution prepared by acetone and pyridine in a volume ratio of 1:0.5, wherein the concentration of the precursor in the acetone / pyridine mixed solution is 10 mg / mL, and then stirring on a magnetic stirrer at a stirring speed of 100 rpm for 36 hours, washing the reaction product with ethanol, centrifuging, and vacuum drying to obtain a graphyne-coated copper nanowire material (product A);
[0047] (2) BiI3 is added to 1,3-dimethylpropyleneurea to dissolve, and then tetrabutylammonium tetrafluoroborate is added thereto to prepare a BiI3 mixed solution (solution B), wherein the concentration of tetrabutylammonium tetrafluoroborate (TBABF4) in the mixed solution is 1 mol / L, and the concentration of BiI3 is 1 mol / L. The BiI3 mixed solution (solution B) and the graphyne-coated copper nanomaterial (product A) in step (1) are mixed on a magnetic stirrer and stirred, wherein the molar ratio of copper to bismuth in the mixed solution is 1:5, the stirring speed is 100 rpm, the reaction is carried out for 36 hours, the product is washed with ethanol, centrifuged, and a tubular graphyne-coated bismuth particle nanomaterial is obtained by vacuum drying.
[0048] (3) Tubular graphyne-coated bismuth particle nanomaterials, carbon black and sodium carboxymethyl cellulose (CMC) were prepared into a slurry in a mass ratio of 8:1:1 and coated on copper foil. The slurry was assembled with lithium metal foil into a half-cell. The separator was glass fiber and the electrolyte was 1M LiPF6 in diethylene glycol dimethyl ether solution. The electrochemical performance of the battery was investigated. -1 At the current density, the capacity is 341mA hg -1 , at 150A g -1 At ultra-high current density, the capacity is 265mA hg -1 , at 10A g -1 After 20,000 cycles at high current density, the capacity retention rate is as high as 94%.
[0049] Example 6
[0050] A tubular Graphene coated Bismuth particle nanomaterial, the preparation method of which comprises the following steps:
[0051] (1) adding copper nanowires with a diameter of 50 nm and deprotected 1,3,5-(trimethylsilyl)ethynyl-2,4,6-triazine (the molar ratio of copper nanowires to 1,3,5-(trimethylsilyl)ethynyl-2,4,6-triazine is 1:10) to a mixed solution prepared by acetone and pyridine in a volume ratio of 1:0.2, wherein the concentration of the precursor in the acetone / pyridine mixed solution is 50 mg / mL, and then stirring on a magnetic stirrer at a stirring speed of 100 rpm for 72 hours, washing the reaction product with ethanol, centrifuging, and vacuum drying to obtain a graphyne-coated copper nanowire material (product A);
[0052] (2) BiI3 is added to 1,3-dimethylpropyleneurea to dissolve, and then tetrabutylammonium tetrafluoroborate is added thereto to prepare a BiI3 mixed solution (solution B), wherein the concentration of tetrabutylammonium tetrafluoroborate (TBABF4) in the mixed solution is 0.5 mol / L, and the concentration of BiI3 is 0.5 mol / L. The BiI3 mixed solution (solution B) and the graphyne-coated copper nanomaterial (product A) in step (1) are mixed on a magnetic stirrer and stirred, wherein the molar ratio of copper to bismuth in the mixed solution is 1:2, the stirring speed is 100 rpm, the reaction is carried out for 36 hours, the product is washed with ethanol, centrifuged, and a tubular graphyne-coated bismuth particle nanomaterial is obtained by vacuum drying.
[0053] (3) Tubular graphyne-coated bismuth particle nanomaterials, carbon black and sodium carboxymethyl cellulose (CMC) were prepared into a slurry in a mass ratio of 8:1:1 and coated on copper foil. The slurry was assembled with sodium metal foil into a half-cell. The separator was glass fiber and the electrolyte was 1M NaPF6 tetraethylene glycol dimethyl ether solution. The electrochemical performance of the battery was investigated. -1 At the current density, the capacity is 376mA hg -1 , at 150A g -1 At ultra-high current density, the capacity is 282mA hg -1 , at 10A g -1 After 25,000 cycles at high current density, the capacity retention rate is as high as 97%.
[0054] Example 7
[0055] A tubular Graphene coated Bismuth particle nanomaterial, the preparation method of which comprises the following steps:
[0056] (1) adding copper nanowires with a diameter of 100 nm and deprotected hexa((trimethylsilyl)ethynyl)benzene (the molar ratio of copper nanowires to hexa((trimethylsilyl)ethynyl)benzene is 1:30) to a mixed solution prepared by acetone and pyridine in a volume ratio of 1:0.5, wherein the concentration of the precursor in the acetone / pyridine mixed solution is 5 mg / mL, and then stirring on a magnetic stirrer at a stirring speed of 100 rpm for 72 hours, washing the reaction product with ethanol, centrifuging, and vacuum drying to obtain a graphyne-coated copper nanowire material (product A);
[0057] (2) BiI3 is added to 1,3-dimethylpropyleneurea to dissolve, and then tetrabutylammonium tetrafluoroborate is added thereto to prepare a BiI3 mixed solution (solution B), wherein the concentration of tetrabutylammonium tetrafluoroborate (TBABF4) in the mixed solution is 1 mol / L, and the concentration of BiI3 is 0.5 mol / L. The BiI3 mixed solution (solution B) and the graphyne-coated copper nanomaterial (product A) in step (1) are mixed on a magnetic stirrer and stirred, wherein the molar ratio of copper to bismuth in the mixed solution is 1:4, the stirring speed is 100 rpm, the reaction is carried out for 72 hours, the product is washed with ethanol, centrifuged, and a tubular graphyne-coated bismuth particle nanomaterial is obtained by vacuum drying.
[0058] (3) Tubular graphyne-coated bismuth particle nanomaterials, carbon black and sodium carboxymethyl cellulose (CMC) were prepared into a slurry in a mass ratio of 9:0.5:0.5 and coated on copper foil. The slurry was assembled with sodium metal foil into a half-cell. The separator was glass fiber and the electrolyte was 2M NaPF6 triethylene glycol dimethyl ether solution. The electrochemical performance of the battery was investigated. -1 At the current density, the capacity is 352mA hg -1 , at 150A g -1 At ultra-high current density, the capacity is 288mA hg -1 , at 10A g -1 After 20,000 cycles at high current density, the capacity retention rate is as high as 97%.
[0059] Example 8
[0060] A tubular Graphene coated Bismuth particle nanomaterial, the preparation method of which comprises the following steps:
[0061] (1) adding copper nanowires with a diameter of 50 nm and deprotected hexa((trimethylsilyl)ethynyl)benzene (the molar ratio of copper nanowires to hexa((trimethylsilyl)ethynyl)benzene is 1:50) to a mixed solution prepared by acetone and pyridine in a volume ratio of 1:1, wherein the concentration of the precursor in the acetone / pyridine mixed solution is 100 mg / mL, and then stirring on a magnetic stirrer at a stirring speed of 100 rpm for 72 hours, washing the reaction product with ethanol, centrifuging, and vacuum drying to obtain a graphyne-coated copper nanowire material (product A);
[0062] (2) BiI3 is added to 1,3-dimethylpropyleneurea to dissolve, and then tetrabutylammonium tetrafluoroborate is added thereto to prepare a BiI3 mixed solution (solution B), wherein the concentration of tetrabutylammonium tetrafluoroborate (TBABF4) in the mixed solution is 0.1 mol / L, and the concentration of BiI3 is 2 mol / L. The BiI3 mixed solution (solution B) and the graphyne-coated copper nanomaterial (product A) in step (1) are mixed on a magnetic stirrer and stirred, wherein the molar ratio of copper to bismuth in the mixed solution is 1:8, the stirring speed is 100 rpm, the reaction is carried out for 72 hours, the product is washed with ethanol, centrifuged, and a tubular graphyne-coated bismuth particle nanomaterial is obtained by vacuum drying.
[0063] (3) Tubular graphyne-coated bismuth particle nanomaterials, carbon black and polyvinylidene fluoride (PVDF) were prepared into a slurry in a mass ratio of 7:2:1 and coated on copper foil. The slurry was assembled with lithium metal foil into a half-cell. The separator was glass fiber and the electrolyte was 1M LiPF6 in ethylene glycol dimethyl ether solution. The electrochemical performance of the battery was investigated. -1 At the current density, the capacity is 348mA hg -1 , at 150A g -1 At ultra-high current density, the capacity is 261mA hg -1 , at 10A g -1 After 10,000 cycles at high current density, the capacity retention rate is as high as 99%.
[0064] Example 9
[0065] A tubular Graphene coated Bismuth particle nanomaterial, the preparation method of which comprises the following steps:
[0066] (1) adding copper nanowires with a diameter of 100 nm and deprotected hexa((trimethylsilyl)ethynyl)benzene (the molar ratio of copper nanowires to hexa((trimethylsilyl)ethynyl)benzene is 1:30) to a mixed solution prepared by acetone and pyridine in a volume ratio of 1:0.2, wherein the concentration of the precursor in the acetone / pyridine mixed solution is 10 mg / mL, and then stirring on a magnetic stirrer at a stirring speed of 100 rpm for 36 hours, washing the reaction product with ethanol, centrifuging, and vacuum drying to obtain a graphyne-coated copper nanowire material (product A);
[0067] (2) BiI3 is added to 1,3-dimethylpropyleneurea to dissolve, and then tetrabutylammonium tetrafluoroborate is added thereto to prepare a BiI3 mixed solution (solution B), wherein the concentration of tetrabutylammonium tetrafluoroborate (TBABF4) in the mixed solution is 1 mol / L, and the concentration of BiI3 is 5 mol / L. The BiI3 mixed solution (solution B) and the graphyne-coated copper nanomaterial (product A) in step (1) are mixed on a magnetic stirrer and stirred, wherein the molar ratio of copper to bismuth in the mixed solution is 1:10, the stirring speed is 100 rpm, the reaction is carried out for 72 hours, the product is washed with ethanol, centrifuged, and a tubular graphyne-coated bismuth particle nanomaterial is obtained by vacuum drying.
[0068] (3) Tubular graphyne-coated bismuth particle nanomaterials, carbon black and polyvinylidene fluoride (PVDF) were prepared into a slurry in a mass ratio of 7:2:1 and coated on copper foil. The slurry was assembled with lithium metal foil into a half-cell. The separator was glass fiber and the electrolyte was 2M LiPF6 in diethylene glycol dimethyl ether solution. The electrochemical performance of the battery was investigated. -1 At the current density, the capacity is 368mA hg -1 , at 150A g -1 At ultra-high current density, the capacity is 301mA hg -1 , at 10A g -1 After 20,000 cycles at high current density, the capacity retention rate is as high as 94%.
Claims
1. A method for preparing a tubular Graphene-coated Bismuth particle nanomaterial, characterized in that: The following steps are involved: (1) using a copper catalyst to catalyze the precursor to perform an alkyne-alkyne coupling reaction to prepare a graphene-coated copper nanomaterial; (2) using an electrochemical replacement reaction to replace the metallic copper in the graphyne-coated copper nanowires with metallic bismuth to obtain; The precursor is ethynylbenzene, and the copper catalyst is copper nanowire.
2. The method for preparing the tubular Graphene-coated Bismuth particle nanomaterial according to claim 1, characterized in that: The copper nanowire has a diameter of 10-200 nm and a length of 0.1-100 μm.
3. The method for preparing the tubular Graphene-coated Bismuth particle nanomaterial according to claim 2, characterized in that: The alkyne-alkyne coupling reaction process in step (1) is as follows: adding the copper catalyst and the precursor to an acetone / pyridine reaction solvent, stirring the reaction for 24-72 hours, and obtaining the graphyne-coated copper nanomaterial.
4. The method for preparing the tubular Graphene-coated Bismuth particle nanomaterial according to claim 3, characterized in that: The molar ratio of copper to the precursor in the copper catalyst is 1:10-100, and the concentration of the precursor in the solution is 0.01-500 mg / mL.
5. The method for preparing the tubular Graphene-coated Bismuth particle nanomaterial according to claim 3, characterized in that: The volume ratio of acetone to pyridine in the reaction solvent is 1:0.1-1.
6. The method for preparing the tubular Graphene-coated Bismuth particle nanomaterial according to claim 1, characterized in that: The specific operation in step (2) is as follows: adding BiI3 to 1,3-dimethylpropyleneurea to dissolve, then adding tetrabutylammonium tetrafluoroborate thereto to obtain a BiI3 mixed solution, mixing the BiI3 solution with the graphyne-coated copper nanomaterial in step (1), stirring the reaction, and obtaining.
7. The method for preparing the tubular Graphene-coated Bismuth particle nanomaterial according to claim 6, characterized in that: The concentration of BiI3 in the BiI3 mixed solution is 0.01-10 mol / L, and the concentration of tetrabutylammonium tetrafluoroborate is 0.01-1 mol / L.
8. The method for preparing the tubular Graphene-coated Bismuth particle nanomaterial according to claim 6, characterized in that: The molar ratio of copper to bismuth in the reaction of step (2) is 1:1-10.
9. A tubular graphyne-coated bismuth particle nanomaterial, characterized in that: The method according to any one of claims 1 to 8 is adopted to prepare the present invention.
10. Use of the tubular graphyne-coated bismuth particle nanomaterial described in claim 9 in preparing a negative electrode material for a sodium ion battery or a negative electrode material for a lithium ion battery.
